2019
DOI: 10.31160/jotci201927a201824
|View full text |Cite
|
Sign up to set email alerts
|

Multivessel myocardial bridge involving left and right coronary arteries

Abstract: A 62-year-old female patient with hypertension and a 4-month history of angina pectoris, triggered by emotional stress. The electrocardiogram showed left ventricular hypertrophy and changes in ventricular repolarization. The coronary angiography showed a significant left ventricular hypertrophy with no intracavitary gradient, and the presence of a myocardial bridge over the middle third of the left anterior descending artery and the right coronary artery in its posterior descending branch. Myocardial bridge al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Although prevalence of MB in various studies has been highly variable, a higher incidence has been observed in patients with hypertrophic obstructive cardiomyopathy (HOCM). [ 5 6 ] It has been observed to be present in up to 86% of cases in autopsy series,[ 7 ] but it was seen only in 0.5–1.6% in most angiographic studies. [ 8 ] Although coronary angiography is considered as a gold standard for diagnosing this entity, other modalities like intravascular sonography and multidetector computed tomography (MDCT) are also useful for diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although prevalence of MB in various studies has been highly variable, a higher incidence has been observed in patients with hypertrophic obstructive cardiomyopathy (HOCM). [ 5 6 ] It has been observed to be present in up to 86% of cases in autopsy series,[ 7 ] but it was seen only in 0.5–1.6% in most angiographic studies. [ 8 ] Although coronary angiography is considered as a gold standard for diagnosing this entity, other modalities like intravascular sonography and multidetector computed tomography (MDCT) are also useful for diagnosis.…”
Section: Introductionmentioning
confidence: 99%